Impact of low loading on digestion of the mechanically-separated organic fraction of municipal solid waste. (15th April 2020) - Zhang, Wei; Venetsaneas, Nikolaos; Heaven, Sonia; Banks, Charles J.
Highlights: OFMSW co-digestion with sewage sludge digestate an effective strategy for low OLR. Energy analysis shows 48% increase in electricity for export, 22% in heat. Mesophilic digestion at low OLR unstable due to low N concentration. Digestate addition limited by N input in thermophilic conditions. Process integration offers a promising route for contaminated feedstocks. Abstract: Changing waste management practice, introduction of new technologies, and population demographics and behaviour will impact on both quantity and composition of future waste streams. Laboratory-scale anaerobic digestion of the mechanically-separated organic fraction of municipal solid waste (ms-OFMSW) was carried out at relatively low organic loading rates (OLR), and results analysed using an energy modelling tool. Thermophilic operation with water addition and liquor recycle was compared to co-digestion with dilution water replaced by sewage sludge digestate (SSD); thermophilic and mesophilic mono-digestion were also tested at low OLR. All thermophilic conditions showed stable operation, with specific methane production (SMP) from 0.203 to 0.296 m 3 CH4 kg −1 volatile solids (VS). SSD addition increased biogas production by 20% and there was evidence of further hydrolysis and degradation of the SSD. Long-term operation at 1 kg VS m −3 day −1 had no adverse effect except in mesophilic conditions where SMP was lower at 0.256 m 3 CH4 kg −1 VS and stability was reduced, especially during OLR increases. This was probably due to low total ammonia nitrogen, which stabilised at 0.2 g N kg −1 and limited the buffering capacity. Energy analysis showed thermophilic operation at OLR 2 g VS L −1 day −1 gave 42% of the theoretical methane potential and 38% of the higher heating value, reducing to 37% and 34% respectively in mesophilic conditions. Scenario modelling indicated that under low ms-OFMSW load even an energy-depleted co-substrate such as SSD could contribute to the energy balance, and would be a better diluent than water due to its nutrient and buffering capacity.